"Our whole domain was a Garret": Robert Bloomfield and Laboring Class Life-Writing. Issue 5 (2nd September 2020) - Ward, Sam
ABSTRACT: Although he was most commonly regarded as a poet of the rural world, Robert Bloomfield's success as a writer is inextricably linked to the urban and artisanal culture that shaped both his sense of self and others' perception of his work. Initially celebrated as a stand-in for "Giles, " the farmer's boy of his first and most successful publication, Bloomfield's status as a ladies' shoemaker at the time of the poem's composition led to the development of a tension between different ways of viewing the author and his achievements. This article brings to light two hitherto neglected works which provide new information about Bloomfield's life prior to achieving fame, and which illuminate his attempts to reconcile his own experience of life with the way in which this was represented and marketed by others.